Functional Self‐Assembled Peptide Nanofibers for Bone Marrow Mesenchymal Stem Cell Encapsulation and Regeneration in Nucleus Pulposus. Issue 6 (6th May 2016) - Wu, Yaohong; Jia, Zhiwei; Liu, Longgang; Zhao, Yachao; Li, Hao; Wang, Chaofeng; Tao, Hui; Tang, Yong; He, Qing; Ruan, Dike
Abstract: Low back pain (LBP) is mainly caused by intervertebral disc degeneration (IDD). Recent studies have demonstrated that the transplantation of mesenchymal stem cells (MSCs) can regenerate regions that have undergone degeneration, and the regenerative effect can be enhanced by using a hydrogel carrier. This article describes an injectable functional hydrogel system manufactured by combining RADA16‐I and RADA‐KPSS (RADA‐KPSS was manufactured by conjugating a bioactive motif derived from BMP‐7 [KPSS] onto the C terminal of RADA16‐I) at a volume ratio of 1:1. This hydrogel system can enhance the proliferation, differentiation, and chemotactic migration of BMSCs. In addition, the encapsulation of BMSCs with this system maintains cell viability for a long period after transplantation into an ex vivo cultured disc model. In conclusion, KPSS‐conjugated RADKPS is an ideal encapsulation system for BMSCs in intervertebral disc (IVD) regeneration.